An integrated packed bed-oscillating heat pipe system for energy efficient isothermal adsorption processes - Yeboah, Siegfried Kwame (2017)
Energy use in buildings accounts for a large portion of global and regional energy demand and energy-related CO2 emissions. To steer the world towards a low carbon future, the development of new and more efficient technologies is required. In hot and humid climates, the high latent heat loads results in uncomfortable and unhealthy indoor environments, accounting for 30% to 50% of standard air conditioning energy requirements. Physical adsorption of water vapour on solid desiccants is found to offer an energy efficient alternative to conventional dehumidification process using standard air conditioning systems. However, the isosteric heat of adsorption released increases the surface vapour pressure of the solid desiccants resulting in a decreased adsorption capacity. In packed beds of solid desiccants, this heat of adsorption increases the bed temperature, exit air temperature and exit air humidity ratio subsequently imposing an increased cooling load requirement and high energy requirement in the regeneration of the solid desiccants. In literature, several approaches used in removing in situ the heat of adsorption released in packed bed systems were fraught with several limitations. To this end, an integrated packed bed-oscillating heat pipe (OHP) system was proposed. The concept was for the evaporator of the OHP to remove the heat of adsorption generated by the packed bed and reject at its condenser towards an energy efficient isothermal adsorption process. To achieve this, theoretical investigations of the individual systems and the integrated systems preceded experimental testing of a rig set up in the laboratory. For the theoretical studies, the OHP was helically coiled at both ends, filled with ethanol, methanol and water working fluids respectively at 50% volume fraction and numerically investigated using the Eulerian Volume of Fluid (VOF) model in ANSYS Fluent R15.0. The packed bed on the other hand was configured as a Heggs et al (1994) Z-type flow arrangement for enhanced radial flow using the Porous Media model in ANSYS Fluent R15.0 set up with the properties of Silica Gel. ANSYS Fluent R15.0 System Coupling limitations led to the development of mathematical models for the prediction of the integrated system performance. The experimental investigations were in line with the theoretical only in this case the optimum working fluid, deionized water, was used as the main working fluid in the helically coiled OHP (HCOHP). The results showed reasonable agreement between the performance of the numerical model and experimental prototype. The HCOHPs were capable of passively removing heat from the packed bed systems. Mean bed temperature reduction between the integrated packed bed-HCOHP system and corresponding individual packed bed configurations were about 5.61°C, 9.48°C and 10.14°C respectively for the large annulus (LAPB), medium annulus (MAPB) and small annulus (SAPB) packed bed configurations. Average packed bed outlet temperature reductions of about 6.61°C, 9.19°C and 6.29°C were also achieved for the respective configurations. A validation of the theoretical model showed average temperature difference of about 5.60°C between the experimental prototype of the integrated system and results predicted using experimental packed bed temperature data and HCOHP thermal resistance. Compared to other similar systems in literature, the integrated packed bed-HCOHP system showed capacity to passively remove significant amounts of the heat of adsorption released in silica gel packed beds towards isothermal adsorption.